Restauración y automatización del banco de pruebas del laboratorio de garantías Schneider Electric Colombia (seco) (2023)
This project focused on the automation of the warranty laboratory of Schneider Electric Colombia in order to improve testing efficiency and ensure operational safety. Through a rigorous methodological approach, an automated system was designed and implemented that integrates command and signaling components, programmable logic controller (PLC) of the Machine offer reference TM221CE40R and human-machine interfaces (HMI) of the MAGELIS STU offer reference HMISTU855, manufactured by Schneider Electric Company.